Effects of Primary Varicocele and Related Surgery in Male Infertility: A Meta-Analysis - Wang, Xinkun; Chen, Tong; Qiu, Junfeng; Wu, Hongwei; Chen, Xuehua; Xuan, Xujun (Frontiers in Surgery, 2020)
Purpose: To investigate the effect of primary varicocele and related surgery in male infertility through meta-analysis. Methods: A systematic search of the literature was conducted using the Medline, Embase, Cochrane, and CNKI databases. The search was up to September 2019. Article selection proceeded according to the search strategy based on Preferred Reporting Items for Systematic Reviews and Meta-analyses criteria. Data were analyzed using RevMan 5.2. A random-effects model was used to calculate the overall combined risk estimates. Results: After screening 687 articles, 4 randomized controlled trials with 349 patients were included. One hundred seventy two patients were addressed in embolization/ligation, with 177 patient's observation treatment. The number of spontaneous pregnancies in the two groups was 41 and 40, respectively. There was no significant difference in pregnancy rate between the operation group and the control group. RR = 1.05 [0.72, 1.54]. Conclusion: There is not enough evidence to explain the surgical treatment of varicocele can improve the natural fertility of the infertile couples, and there is still a need for most of prospective randomized controlled trials to verify the efficacy of varicocele surgery for treating of male infertility. We do not deny the importance of this operation, we just want to call on everyone to strictly grasp the indications of the operation, avoid ineffective medical expenses, and avoid unnecessary pain to patients.